2013
DOI: 10.1073/pnas.1304592110
|View full text |Cite
|
Sign up to set email alerts
|

Kelch-like 3 and Cullin 3 regulate electrolyte homeostasis via ubiquitination and degradation of WNK4

Abstract: Pseudohypoaldosteronism type II (PHAII) is a rare Mendelian syndrome featuring hypertension and hyperkalemia resulting from constitutive renal salt reabsorption and impaired K + secretion. Recently, mutations in Kelch-like 3 (KLHL3) and Cullin 3 (CUL3), components of an E3 ubiquitin ligase complex, were found to cause PHAII, suggesting that loss of this complex's ability to target specific substrates for ubiquitination leads to PHAII. By MS and coimmunoprecipitation, we show that KLHL3 normally binds to WNK1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
203
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 215 publications
(212 citation statements)
references
References 22 publications
6
203
1
2
Order By: Relevance
“…Interestingly, S433 is recurrently mutated in autosomal dominant PHAII (4,26). Mutation of S433 abrogates WNK4 binding and degradation, increasing WNK4 levels (22,23). This observation suggested that S433 phosphorylation might modulate KLHL3 binding and degradation of WNK4.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Interestingly, S433 is recurrently mutated in autosomal dominant PHAII (4,26). Mutation of S433 abrogates WNK4 binding and degradation, increasing WNK4 levels (22,23). This observation suggested that S433 phosphorylation might modulate KLHL3 binding and degradation of WNK4.…”
Section: Resultsmentioning
confidence: 95%
“…We quantitated WNK4 levels when expressed with either KLHL3 WT or KLHL3 S433E (23). As reported (23), KLHL3 WT reduced WNK4 levels by 57% (P = 0.002; Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations